Effects Of Globalization On Tourism Development In Vietnam - Truong Thi Xuan Dao; Made Sukana; Nguyen Thi Kim Duyen; Nguyen Lam Ngoc Vi (JURNAL DESTINASI PARIWISATA, 2022)
Tourism is one of the typical examples of globalization. This paper aims to analyze and assess howglobalization has impacted tourism development in Vietnam. Analyzing the positive and negative impacts ofglobalization on tourism development will provide an overview of what is happening in the context of Vietnambecoming one of the Asia countries having the highest tourism growth today. To take advantage of the positive effectsof globalization in tourism development and minimize the negative impacts that globalization brings, Vietnam needsto have sustainable tourism development orientations.Keywords: Vietnam Tourism, Tourism Development, Globalization.